Assessment of the frequency of routine removal of dental plaque prior to caries diagnosis by dentists in three cities in southern Brazil - Carlos Heitor Cunha Moreira; Julio Eduardo do Amaral Zenkner; Eduardo Machado; Rachel de Oliveira Rocha; Luciano Casagrande; Cassiano Kuchenbecker Rosing (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The aim of this study was to assess the frequency of routine use of dental prophylaxis prior to visual inspection, in order to diagnose caries, by dentists with different lapses of time after graduating time. One hundred and fifty one Brazilian dentists were interviewed in 3 Brazilian cities to determine if they usually remove dental plaque prior to visual inspection for caries diagnosis. The dentists were stratified according to year of graduation. The association between the lapse of time after graduating and the practice of routinely removing dental plaque before clinical examination was tested using the chi-square test with a significance level of 5%. Only 28.5% of the dentists reported that they usually remove dental plaque prior to clinical examination. The dentists who graduated in the last 15 years presented the lowest percentages of plaque removal prior to clinical examination (15.1%), whereas the more experienced dentists reported that they perform prophylaxis more frequently. Of the professionals who graduated from 1960-1975, 23.9% reported that they performed dental plaque removal prior to diagnosis, whereas the figure for those graduating from 1976-1990 was 46.2%. Most of the dentists interviewed reported that they did not remove dental plaque prior to performing visual diagnosis of caries.